Case Report: A Case of Eyelid Myoclonic Status With Tonic–Clonic Seizure and Literature Review - Yuan, Yujun; Yang, Fenghua; Huo, Liang; Fan, Yuying; Liu, Xueyan; Wu, Qiong; Wang, Hua (Frontiers in Pediatrics, 2021)
Eyelid myoclonus with or without absence epilepsy is a rare and usually misdiagnosed disease in the neurology department. It is an idiopathic general epileptic syndrome, the onset period is 6–8 years, and is more common in girls. It is characterized by rapid abnormal eye blinking, accompanied by upward rolling of the eye and slight backward movement of the head, with eye closure sensitivity and photosensitivity. The seizure is frequent and short, dozens or even hundreds of times a day; a small number of patients may have eyelid myoclonus status. We report a patient who visits the hospital for the first time with eyelid myoclonic problem; the patient continued to wink the eyes, eye rolled up, and backward movement of the head, accompanied by impairment of consciousness. Video electroencephalography (VEEG) suggests continued spike slow-wave, polyspike slow-wave. After the patient had 2, 4, 6, 8, 10, 12, and 14 Hz of intermittent photic stimulation (IPS), her seizures and epileptic discharges reduced or stopped. Seven min after giving stimulation at 20 Hz, the child developed an occipital-initiated tonic–clonic seizure, which demonstrated that after sufficient IPS stimulation, the occiput cortex became excited and initiated a brain network, leading to diffuse brain discharge and tonic–clonic seizures. At 1 h after onset, the child developed a nonconvulsive state, with impairment of consciousness despite no eyelid myoclonic movements, and VEEG suggested a large number of epileptic discharges. After 10 min of administrating midazolam, the patient's EEG immediately became normal, and the patient regained consciousness. Therefore, this paper presents an eyelid myoclonus status patient with occipital origin seizure, we recorded the whole course of the disease and the treatment effect, and reviewed the literature accordingly.